Efficacy of Monopolar Radiofrequency in Middle and Lower Face Laxity (Annals of Medical Research, 2021)
Aim: In recent years, radiofrequency (RF) systems have become one of the most commonly used rejuvenation methods, especially in the skin of the mid-lower face. In this study, the efficacy of monopolar RF energy in mid-lower face skin sagging was evaluated.
Keywords: Radiofrequency; Monopolar Radiofrequency; Laxity; Rejuvenation.